Identification and characterization of the Tupaia herpesvirus DNA polymerase gene. - Springfeld, Christoph; Tidona, Christian; Kehm, Roland; Bahr, Udo; Darai, Gholamreza (Journal of general virology, 1998)
Tupaia herpesviruses (THVs) have been isolated from malignant lymphomas and from degenerating lung or spleen cell cultures of tree shrews (Tupaia spp.), but because of a lack of genetic information the final classification of THVs is still open. In the present work the viral DNA polymerase (DPOL) gene was mapped within the genome of the different THV strains using PCR and degenerate oligonucleotide primers. Nucleotide sequences of the DPOL genes of THV strains 1 to 5 were determined and used for comparative analyses. The transcriptional activity of the THV-2 DPOL gene was confirmed by RT-PCR. It was found that the different THV strains are very closely related to each other. When compared to other herpesviruses the highest amino acid sequence identities detected were with DPOLs of the murine and human cytomegaloviruses. These results justify the conclusion that THVs are members of the subfamily Betaherpes- virinae.
Gesehen am 05.09.2024